2008
DOI: 10.3354/meps07259
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental settings on the prevalence of Trichodesmium spp. in the Bay of Bengal

Abstract: Trichodesmium, an important marine nitrogen-fixing cyanobacteria, is widespread in tropical waters and contributes substantially to the global chemical cycles by new production. The interesting and intriguing feature of Trichodesmium blooms is the suddenness with which the blooms appear and disappear. A well-defined periodicity and annual rhythm of Trichodesmium blooms in the Indian south central coastal environments of the Arabian Sea between February and May is well documented. However, not much is known for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 41 publications
(39 reference statements)
1
17
0
Order By: Relevance
“…Cyanobacteria and other phytoplankton blooms have been reported in many coastal waters and marginal seas, such as in the Gulf of Finland and the Baltic Sea [ Bianchi et al , 2000; Hansson and Hakansson , 2007], Lake Erie [ Vincent et al , 2004], the Bay of Bengal [ Hegde et al , 2008], and Moreton Bay, Australia [ Roelfsema et al , 2006]. The West Florida Shelf in the eastern Gulf of Mexico is also known to experience periodic occurrence of cyanobacteria ( Trichodesmium spp . )…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacteria and other phytoplankton blooms have been reported in many coastal waters and marginal seas, such as in the Gulf of Finland and the Baltic Sea [ Bianchi et al , 2000; Hansson and Hakansson , 2007], Lake Erie [ Vincent et al , 2004], the Bay of Bengal [ Hegde et al , 2008], and Moreton Bay, Australia [ Roelfsema et al , 2006]. The West Florida Shelf in the eastern Gulf of Mexico is also known to experience periodic occurrence of cyanobacteria ( Trichodesmium spp . )…”
Section: Discussionmentioning
confidence: 99%
“…It forms dense blooms which are studied with the purpose of understanding both its biomass as well as its distribution (Capone et al, 1997;Carpenter and Price, 1977). Since 1950, these blooms have been reported in the Arabian Sea (Basu et al, 2011;Capone et al, 1998;Desa et al, 2005;Devassy et al, 1978;Lugomela et al, 2002;Parab et al, 2006;Ramamurthy et al, 1972;Sawant and Madhupratap, 1996), the Lakshadweep Sea (Qasim, 1970), the Andaman Sea (Jyothibabu et al, 2003) and the Bay of Bengal (Hegde et al, 2008;Jyothibabu et al, 2003). The phytoplankton biomass at times exceeds 100 μgL −1 during the blooming period this value is higher than any other biomass value recorded in any other individual species (Parab et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…In addition, the study successfully validated the algorithm using SeaWiFS match-up scenes containing in situ observations of Trichodesmium. Furthermore, Hedge et al (2008) found the algorithm did not yield false-positive retrievals for pixels that were known not to contain Trichodesmium.…”
Section: Chlorophyll Enrichment In the South-west Pacific Oceanmentioning
confidence: 97%
“…Although, this study did not focus on algorithm development, it demonstrated how a suitable Trichodesmium remote-sensing algorithm could be applied in a useful way. The work of Hedge et al (2008) successfully determined a month-by-month climatology of the spatial distribution of Trichodesmium which was then linked with information regarding SST, nutrient regime and ocean currents. In addition, the study successfully validated the algorithm using SeaWiFS match-up scenes containing in situ observations of Trichodesmium.…”
Section: Chlorophyll Enrichment In the South-west Pacific Oceanmentioning
confidence: 99%
See 1 more Smart Citation